PENGEMBANGAN MEDIA MADING INTERAKTIF PADA PEMBELAJARAN IPAS MATERI TRADISI KELUARGA DAN MASYARAKAT PADA KELAS III SD - Fadilah, Qudrotul; Marini, Arita; Hadi, Waluyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted because science and social studies (IPAS) learning in Grade III still relied on simple learning media, creating a need for more engaging instructional materials. The study aimed to develop an interactive bulletin board learning media for the topic